Salt & stone - Scott, Victoria (Young adult author) (Scholastic Press, 2015)
Tella will have to face the unseen dangers of the ocean, the breathless cold of a mountain, and twisted new rules in the Brimstone Bleed for a chance at obtaining the Cure for her brother.